STRATEGI PEMASARAN AGROINDUSTRI KERIPIK TEMPE DI DESA BULUH RAMPAI KECAMATAN SEBERIDA KABUPATEN INDRAGIRI HULU (Studi Kasus Agroindustri Keripik Tempe Dua Putri Mbak Siti) - NIRMALA SARI; EVY MAHARANI; SHOREA KHASWARINA (Jurnal Ilmiah Pertanian, 2016)
This study aimed to identify the aspects of the strengths, weaknesses, opportunities and threats facing the agroindustry marketing of Dua Putri tempe chips and formulate marketing strategies Dua Putri tempechips agroindustry by using SWOT analysis. The results showed that internal factors encountered in the marketing of Dua Putri tempeagro-chips in Indragiri Hulu is Strength: choose a label and branded products, entrepreneurs have a long experience, the product is attractive enough for all people, and the products do not use preservatives. Weakness: The product can be easily damaged and destroyed, packaging using a simple wrapper, product marketing has not come out Indragiri Hulu, and promotion is still limited. External factors include: Opportunities: products already well known, a product that can compete with similar products, the market is still wide open, the exhibition and promotion opportunities. Threat; Many competitors of similar products, the market demand fluctuates, and the limitations of market information and for marketing strategies Dua Putritempechips agroindustry is to maintain existing markets and seek new markets including exhibition, the exhibition is there to improve their skills in providing products with flavor worth nutrition, make packaging more attractive in order to reach the marketing of products inside and outside the district, improve the taste and quality and maximize promotion, looking for alternative marketing channels.